Faktor Penyebab Ketidaklengkapan Pengisian Kode Diagnosa Rawat Jalan di RS Husada Utama - Nabiilah Qurrota A'yun; Rossalina Adi Wijayanti; Gilang Nur Permana; Ida Nurmawati (Politeknik Negeri Jember, 2020)
At present hospitals and paramedics prone to demands that demands the quality of service , lawsuits from a patient and the competitors in the same because of that required to improve the quality and keep the quality of health services at the hospital .One parameter to determine the quality of health services at the hospital is data or information from medical record good and complete , both the contents , accurate , timely and working persayaratan legal aspects .Based on working practices roomy implemented in february to march obtained hasill that incomplete filling out of code diagnose on medical record outpatient husada surabaya hospital main reach 100 % it is not in line with permenkes 269 year 2008 stating that document completeness medical record must be fully 100 %. A journal aims to understand the factors causing the incomplete filling out of the diagnosis code .Incompleteness this researched use the undirected behavior lawrence green with a variable presdiposing factors , enabling options factors , reinforcing factors .Incomplete filling out of the diagnosis code was conducted by interviews is not structured and observation activities directly when performing my roomy .The result of the report is affecting behavior because of the incomplete on charging the diagnosis code outpatient medical record husada hospital as much as the main the hospitals are required to carry out socialization of standard operating procedures aimed at the paramedics to be the remembrance of the content and doing the work of in accordance with the sop.